Kadar Senyawa Kimia Toksik dalam Darah Ikan Nila (Oreochromis niloticus) Saat Musim Up-Welling di Danau Maninjau, Sumatera Barat - Maharani, Ade Dewi; Susanti, Silvi; Reza, Fachrul (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
Maninjau lake is the largest center for the freshwater floating-net-cage fisheries system in West Sumatra. Every year, during the up-welling season, a huge number of fish suffered to death in the lake including nile tilapia (Oreochromis niloticus), a common species cultivated in the floating-net cages. This current study aimed to determine the factors contributing to the death of fish by measuring the concentration of toxic chemical substances in the blood plasm of nile tilapia as well as in the subtrate collected from the bottom of the lake. The samples were collected in the sites with higher number of floating-net cages as well as higher number of mass death of fish (Tanjung Sani, Pakan Rabaâ€™a dan Maninjau) during the up-welling season. The result revealed that the levels of phosphate, nitrate, nitrit, and amonium were higher in the blood plasm of the fish (87, 216, 13.9, 0.6, dan 5.5 mg/l). Moreover, the levels of those chemical substances were also higher in the substrate of the lake (82.150, 0.546, 33.166, 23.954 dan 0.0776 mg/l). The higher concentration of the toxic chemical substances might contribute to the mass death of fish living in the floating-net cages during the up-welling season.Â